Rostlinné přípravky v terapii benigní hyperplazie prostaty - Sychrová, Alice (Medicína pro praxi, 2023)
Benign prostatic hyperplasia affects men from the age of 40 and its prevalence increases with age. Millions of men worldwide suffer from this disease, with many of them choosing an alternative treatment approach using phytotherapeutics, which are available in the form of registered preparations or food supplements. These preparations contain extracts that have been tested in clinical studies. Many of these studies have been critically evaluated by systematic reviews and meta-analyses. Recent data shows that saw palmetto (Serenoa repens) has a significant effect. Other drugs used in the treatment of BPH/LUTS include stinging nettle, lycopene, pumpkin, pygeum and rye pollen. However, the results of studies cannot be extrapolated to specific products unless proper extraction techniques, phytochemical analysis and dosage have been followed. The present paper aims to provide an overview of the latest knowledge in the field of BPH/LUTS phytotherapy with an emphasis on the clinical effect, side effects, interactions and rational dosage.
Keywords: Phytotherapy; lykopen; Cucurbita; fytoterapie; Prunus africana; lidé; symptomy dolních močových cest; Plant Extracts; rostlinné extrakty; hyperplazie prostaty; Lower Urinary Tract Symptoms; Lycopene; Serenoa; Urtica dioica; Humans; Prostatic Hyperplasia